(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Matius P, Tjwa SJM, Raharja M, Sapruddin, Noor S, Ruslim Y. 2018. Plant diversity in traditional fruit gardens (munaans) of Benuaq and Tunjung Dayaks tribes of West Kutai, East Kalimantan, Indonesia. Biodiversitas 19: 1280-1288. Munaans are traditional fruit gardens of the Benuaq and Tunjung Dayaks tribes of West Kutai, East Kalimantan, Indonesia. This research was conducted in Mencimai, a Benuaq Dayak’s village and Sekolaq Darat, a Tunjung Dayak’ village. A 1.0 ha plot of old munaan lou (lembo lamin) in Mencimai Village was used as representative study site for Benuaq ethnic traditional fruit garden and 1.0 ha plot of old munaan luuq (lembo lamin) in Sekolaq Darat Village as the study site representing Tunjung ethnic fruit gardens. Index of diversity was calculated by using Shannon-Wiener (H’) formulae and evenness by using Pielou. Species richness in munaan lou of Mencimai was 174 and munaan luuq of Sekolaq Darat was 165, which consisted of trees and understorey plants such as tree saplings, seedlings, shrubs, herbs, bamboos, lianas, and rattans. Diversity indices (H’) for all stage of plants within both munaan lou of Mencimai and munaan luuq of Sekolaq Darat were 4.45 and 4.21 with the evenness (E) were 0.86 and 0.82 respectively. The common species of fruit trees found in munaan lou of Mencimai were Lansium domesticum, Durio zibethinus, Nephelium sp., Artocarpus integer, Nephelium lappaceum, Baccaurea macrocarpa, and Baccaurea edulis. Meanwhile, D. zibethinus, L. domesticum, Artocarpus anisophyllus, A. integer, Nephelium uncinatum, and B. macrocarpa were the common fruit species in munaan luuq of Sekolaq Darat. The munaans serve many functions in the local context, and the local communities mainly use them as sources of fruits, wood, medicinal plants, tools, and legality of land tenure.